(untitled) (gjstudies, 2019)
This research introduces a novel, multi-lens theoretical framework to investigate the underexplored causal pathways through which ownership structure shapes accounting policy choices anddisclosure levels. Moving beyond traditional agency theory and principal-agent paradigms, weintegrate insights from behavioral finance, institutional theory, and information economics topropose that ownership influence operates through three distinct, yet interconnected, channels:the *cognitive governance channel*, where owner heuristics and risk perceptions directly biaspolicy selection; the *institutional legitimacy channel*, where ownership composition signalsconformity pressures to external stakeholders, affecting disclosure depth; and the *resource allocation channel*, where ownership concentration determines the strategic resources devotedto financial reporting sophistication. We test this framework using a unique, hand-collectedlongitudinal dataset of 450 publicly traded firms over a ten-year period, employing a hybridmethodological approach that combines explainable machine learning (specifically, SHAP valueanalysis from a Gradient Boosting model) with structural equation modeling. This allows usto move from correlation to causal inference while maintaining interpretability. Our resultsreveal several counterintuitive findings: (1) moderate institutional ownership, rather than highconcentration, correlates with the most aggressive, income-increasing policy choices, contrary toconventional monitoring hypotheses; (2) family ownership, often associated with opacity, leadsto significantly higher voluntary disclosure on long-term strategic risks but lower disclosure onexecutive compensation, a nuanced pattern explained by socioemotional wealth preservation;and (3) the presence of transient institutional investors amplifies the use of complex, obfuscating accounting estimates, not for manipulation but as a rational response to shortened investorhorizons and heightened litigation fears. The study makes an original contribution by decoupling the monolithic concept of ’ownership influence’ into its constituent mechanistic pathways,providing a granular, dynamic model that explains heterogeneous outcomes in financial reporting behavior. Our findings have profound implications for regulators, standard-setters, andinvestors seeking to predict and interpret financial reporting strategies not merely as functionsof ownership type, but as emergent properties of the underlying cognitive, institutional, andresource-based pressures exerted by different owner constellations.